2010
DOI: 10.1029/2010gc003200
|View full text |Cite
|
Sign up to set email alerts
|

Upper mantle structure beneath Cameroon from body wave tomography and the origin of the Cameroon Volcanic Line

Abstract: [1] The origin of the Cameroon Volcanic Line (CVL), a 1600 km long linear volcanic chain without age progression that crosses the ocean-continent boundary in west-central Africa, is investigated using body wave tomography. Relative arrival times from teleseismic P and S waves recorded on 32 temporary seismic stations over a 2-year period were obtained using a multichannel cross-correlation technique and then inverted for mantle velocity perturbations. The P and S wave models show a tabular low-velocity anomaly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
130
3

Year Published

2014
2014
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 101 publications
(150 citation statements)
references
References 80 publications
17
130
3
Order By: Relevance
“…This conclusion was further supported by the results of a more recent H-k stacking analysis of receiver functions using the same data set [Gallacher and Bastow, 2012]. Reusch et al [2010], using body wave tomography, imaged a uniform, vertically oriented, tabular low velocity zone directly below the CVL extending to at least 300 km depth. Using P-wave receiver functions to image the 410 and 660 km discontinuities, Reusch et al [2011] showed that the transition zone beneath the CVL has not been thinned, indicating that the tabular LVZ in the upper mantle does not extend as deep as the transition zone.…”
Section: Previous Geophysical Studiessupporting
confidence: 64%
See 4 more Smart Citations
“…This conclusion was further supported by the results of a more recent H-k stacking analysis of receiver functions using the same data set [Gallacher and Bastow, 2012]. Reusch et al [2010], using body wave tomography, imaged a uniform, vertically oriented, tabular low velocity zone directly below the CVL extending to at least 300 km depth. Using P-wave receiver functions to image the 410 and 660 km discontinuities, Reusch et al [2011] showed that the transition zone beneath the CVL has not been thinned, indicating that the tabular LVZ in the upper mantle does not extend as deep as the transition zone.…”
Section: Previous Geophysical Studiessupporting
confidence: 64%
“…These slow velocities are separated from the fast velocities beneath the Congo Craton by a vertical boundary that extends to at least 200 km, although the velocity contrast across the boundary decreases with depth. These results, together with evidence from body wave [Reusch et al, 2010] and transition zone receiver function [Reusch et al, 2011] studies, create a clear model of a vertical low velocity zone beneath the CVL that extends from the base of the crust to depths between 200 and 300 km, but not into the upper mantle transition zone. These observations are used to evaluate candidate origin models for the formation of the CVL in section 5.2.…”
Section: Lithospheric Instabilitymentioning
confidence: 99%
See 3 more Smart Citations